KNOWLEDGE OF DRUG USE OF TYPE 2 DIABETIC OUTPATIENTS AT DONG THAP REGIONAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: To survey knowledge of drug use of type 2 diabetic outpatients at Dong Thap Regional General Hospital. Objects and methods: retrospective descriptive study on 240 patients diagnosed with type 2 diabetes and outpatient treatment at Dong Thap General Hospital. Results: Patient’s knowledge about antidiabetic drugs was not high: 90.87% of patients did not know the name of the drug which they were taking, 84.35% of patients did not know the side effects of the drug, 40.87% of patients did not know what to do or would take a double dose of the next dose. The average score of knowledge was 2.38 ± 1.81 points. There was a relationship between the patient’s age, education and knowledge score of antidiabetic drugs. There was no relationship between sex and patient’s antidiabetic drug knowledge score. There was a relationship between knowledge score of antidiabetic drugs and adherence to treatment and the result of plasma glucose control. Conclusion: Patient’s knowledge about antidiabetic drugs was not high. The average score of knowledge was 2.38 ± 1.81 points. There was a relationship between the patient’s age, education and knowledge score of antidiabetic drugs. There was a relationship between patient’s knowledge score of antidiabetic drugs and adherence to treatment and the result of plasma glucose control.
Keywords: Type 2 diabetes mellitus, knowledge of drug use, outpatient.